Design and Implementation of an Autonomous USV in Bathymetric Surveys - Xuan-Dung Nguyen; Trung-Kien Vo; Dinh-Hoang Van; Manh-Tuan Ha (International Journal of Intelligent Systems and Applications in Engineering, 2022)
This paper describes the system configuration and control method of an autonomous Unmanned Surface Vehicle (USV) and its implementation in bathymetric surveys. The USV prototype, power unit, control unit, sensory system and communication system are designed and constructed. The control method for a path-following problem is designed and then embedded into the USV’s control unit. The complete USV is then implemented in bathymetric surveys. During each survey, the ground control station (GCS) sends a survey request containing the survey path’s parameters, which consist of the coordinates defining the area of interest and the map resolution. Upon receiving the survey request, the USV automatically calculate the set of waypoints from the parameters in the request. The USV move to each waypoint, collecting the depth data in the process. The USV’s coordinates and the corresponding depth the is continuously sent to the GCS. The survey data is saved on the GCS and then used to build the depth map of the area of interest.